KEWAJIBAN BERBUSANA DAN PEMBENTUKAN JIWA KEAGAMAAN PESERTA DIDIK (Dampak Kebijakan SMP Negeri 1 Kecamatan Jetis Ponorogo) - Nurul Iman; Syamsul Arifin (Universitas Muhammadiyah Ponorogo, 2015)
This research aims to describe moslem dress policy strategy and its impact on religious life of SMP Negeri I Jetis Ponorogo learners. This research is a qualitative research, using passive participant observation, structured interview, and documentation, then analyzed with a qualitative descriptive analysis. From the study, it was found that policy implementation strategy of moslem dress was based on the agreement between school, parents, and students. There was no compulsion on the learners to wear the moslem dress at school, indeed, it was their own awareness to wear this moslem dress as the obligation of Moslem based on al-Quran and al-Hadist. The impact of the moslem dress policy implementation, combined with other religious habituation, showed that it was able to direct the students thought and mental development towards the better direction; It was also able to make the students social life more controlled, make the students having more religious daily life both at school and home, as reflected on the students manners and morals.